Global, regional, and national survey on burden and quality of care index (QCI) of nasopharyngeal cancer: A systematic analysis of the Global Burden of disease study 1990–2019 - Saba Ilkhani; Sahar Saeedi Moghaddam; Delaram Sakhaei; Mohammad-Mahdi Rashidi; Sina Azadnajafabad; Mohammadreza Azangou-Khyavy; Naser Ahmadi; Ozra Tabatabaei-Malazy; Mohammadreza Naderian; Erfan Ghasemi; Parnian Shobeiri; Sahar Mohammadi Fateh; et al. (Oral Oncology Reports)
Background: The epidemiology and inequitable management of nasopharyngeal cancer (NPC) have long been a source of interest due to the malignancy's distinctive geographic distribution. Objective: This study evaluates NPC burden and it's quality of care by socio-demographic index (SDI) groups and world regions from 1990 to 2019. Methods: We gathered epidemiologic metrics (incidence, prevalence, mortality, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) from Global Burden of Disease (GBD) study data. The quality-of-care index (QCI) was rescaled to 0–100 using principal component analysis (PCA). Results: Global NPC incidence rose 161.4 % from 1990 to 2019. However, low and low-middle-income countries experienced a decline. While the all-age crude incidence has risen, DALYs and mortality decreased. NPC's QCI in 2019 was 80.3, increased 110.2 % from 1990. Nevertheless, QCI growth rates were not uniform across SDI categories. High-middle SDI nations improved from 41.8 to 94.1, whereas low SDIs improved from 14.8 to 16.9. In 2019, Singapore (100.0) had the highest, while Somalia (13.2) had the lowest QCI. Young people (<40) receive the best care at almost all SDI levels, and the gender gap is shrinking in lower SDI quantiles with time. Conclusion: The quality of care in all nations and regions has increased over time. However, the disparity between locations is widening. Significantly greater care is offered in nations with high or above-average financial status. Regarding the role of different risk factors on NPC, additional sub-analyses based on different subtypes of NPC in various parts of the world are warranted.